Effects of High Haemoglobin Levels in Pregnancy and their Complications on Maternal and Foetal Outcomes - Reddy, Mule Narasimha Rohith; Fareeha, Shaik Chilabanda; Surendra, Golla; Bai, Mudavath Kusha; Swapna, Masapogu (Indian Journal of Pharmacy Practice)
High haemoglobin levels during pregnancy are increasingly recognized as a potential risk factor for adverse maternal and foetal outcomes. The development of the foetus and the overall results of the pregnancy are greatly influenced by the health of the mother throughout this crucial time. Although iron deficiency and anaemia are well-known issues, high maternal haemoglobin levels have gotten relatively less attention despite the problems they may pose. The many impacts of elevated haemoglobin levels during pregnancy are examined in this paper, along with the implications for the health of the mother and the foetus. Elevated haemoglobin is linked to increased maternal hepcidin levels, disrupting iron transfer to the foetus and potentially leading to intrauterine growth restriction and foetal hypoxia. High maternal haemoglobin levels have been connected to negative outcomes such preeclampsia, gestational diabetes, hypertension, and postpartum problems, yet they are sometimes misunderstood as signs of excellent health. The main cause of these dangers is the inability of plasma volume expansion to occur, which results in higher blood viscosity. High levels of haemoglobin can also hinder the exchange of nutrients between the mother and the foetus, limiting the growth of the foetus and raising the risk of low birth weight, preterm birth, small-for-gestational-age babies, and even stillbirth. Iron homeostasis is further upset by elevated hepcidin levels linked to high haemoglobin, which may result in iron shortage in the foetus. In light of these results, it is crucial to closely monitor haemoglobin levels during pregnancy in order to maximize outcomes for both the mother and the foetus. Future studies should concentrate on identifying at-risk groups to reduce problems, highlighting the need of balanced maternal nutrition, and improving clinical guidelines for haemoglobin management.
Keywords: Haemoglobin; Preeclampsia; Hepcidin; Hypertension